Your pregnancy after 35 - Curtis, Glade B. (Da Capo Lifelong, a member of the Perseus Books Group, 2013)
"please file under Pregnancy: Today, 1 in 5 women in the United States has her first child after age 35; when a woman becomes pregnant in her late thirties or forties, she naturally has different needs than younger mothers-to-be. Now, after more than ten years, Your Pregnancy After 35 has been fully revised with the most up-to-date information, addressing every health and lifestyle concern pertinent to "older" mothers. From how age affects pregnancy to when to consider genetic counseling to how to find the best care when returning to work, this essential guide offers mothers--and their partners--the wise and supportive answers they need"--